The Application of Discovery Learning Model Assisted by Multi-Representation-Based Teaching Materials on Ecosystem Materials to Improve Students' Critical Thinking Ability and Independent Learning Attitudes - Noeryana, Dyah Vita; Mubarok, Ibnul (Journal of Biology Education, 2022)
The purpose of this study is to analyze the effectiveness of the discovery learning assisted by teaching materials based on multi-representation to improve students' critical thinking skills and independent learning attitudes. The research applied used a pre-experiment type one group pretest-posttest design. The population in this study were students of class X MIPA SMA N 1 Kayen for the academic year 2020/2021. The samples in this study were students of class X MIPA 2 and X MIPA 7. The results showed that the two sample classes experienced an increase in critical thinking skills of 0.54 in the medium category and an increase in independent learning attitudes by 0.45 in the medium category. Before treatment, the pretest results were obtained with the results of 1.39% being a very critical category, 9.72% critical, 38.89% quite critical, and 50% less critical. After being treated with the application of the discovery model with multi-representation-based learning tools, the post test results showed that 26.39% of students were in the very critical category, 61.11% in the critical category, and 12.5% ​​in the moderately critical category. From the results of the N-Gain test, students experienced an increase of 18.06% in the high category, 65.28% in the medium category, and 16.67% in the low category. Classically, 81.94% of students complete the KKM. The independent learning attitude of students has increased by 0.45, namely in the medium category. Students experienced an increase of 18.03% in the high category, 63.89% in the medium category, and 18.06% in the low category. Before learning, 25% of the students were in the very independent category, 63.89% of the students were in the independent category, and 11.1% of the students were in the moderately independent category. After learning, 80.56% of students in the very independent category, 18.05% of students in the independent category, and 1.39% in the moderately independent category. Based on the results of the study, it can be concluded that the application of the discovery learning with multi-representation-based learning tools on ecosystem materials is effective for improving students' critical thinking skills and independent attitudes.